Expression of klotho and β‐catenin in esophageal squamous cell carcinoma, and their clinicopathological and prognostic significance. Issue 3 (6th October 2014) - Tang, X.; Fan, Z.; Wang, Y.; Ji, G.; Wang, M.; Lin, J.; Huang, S.
Summary: Esophageal carcinoma is one of the most common types of cancers in the world; the molecular mechanism underlying its tumorigenesis is still not well understood. This study was aimed at investigating the expression of klotho and β‐catenin in patients with esophageal squamous cell carcinoma (ESCC) and analyzing their association with clinicopathological variables and their effects on prognosis. The expression patterns of klotho and β‐catenin were determined by tissue microarray and immunohistochemical technique in ESCC and normal tissues, and their correlations with clinicopathological characteristics were investigated using univariate and multivariate analysis. The serum klotho levels in 40 ESCC patients and controls were measured by sandwich enzyme‐linked immunosorbent assay system (ELISA). The expression level of klotho was significantly lower in ESCC than in the adjacent noncancerous tissues (30 vs. 50%, P < 0.000), and the protein level was negative correlated with clinical staging, histological grade, lymph node metastasis, and invasion depth ( P < 0.05). Whereas, the expression of β‐catenin was much higher in ESCC than their corresponding normal mucosa tissues (78.3 vs. 11.5%, P < 0.000), and the level of protein correlated only with histological grade and invasion depth ( P < 0.05). Correlation analysis showed the expression level of klotho inversely correlated with that of β‐catenin ( r = −0.214, P < 0.01). Patients with klotho‐positive tumors had longer survival than those with klotho‐negative tumors ( P < 0.01). Cox proportional hazards model analysis demonstrated that positive expression of klotho was an important factor indicating good prognosis (hazard ratio, 0.371; 95% confidence interval, 0.201–0.685; P < 0.01). ELISA showed that the level of serum klotho was markedly higher (461.50 ± 43.30 pg/mL) than control group (239.37 ± 20.65 pg/mL) ( P < 0.001). Receiver operating characteristic analysis gave a cut‐off value of 327.031 of serum klotho with a sensitivity of 81.3% and specificity of 81.2% ( P < 0.000). Our present study demonstrated for the first time that klotho might be a novel biomarker candidate for predicting progression and prognosis in patients with ESCC.